PERSEPSI PENGUNJUNG TERHADAP FASILITAS TAMAN OLAH RAGA DAN REKREASI (TORR) RUMBAI KOTA PEKANBARU - Sweny Savela Sabilla; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Sports and Recreation Park facilities (TORR), are facilities for the public to do sports and recreation, but currently many sports and recreation park facilities are no longer suitable for use, many are damaged, have holes, the grass is high and some are missing. the grass and the saddest thing near the goal is used for selling. The electric light is off, the toilet is open, there is no roof and there is no water, the garbage is scattered, etc. For this reason, the problems that can be raised are: 1). What is the visitor's perception of the sports and recreation park facilities and 2). What factors cause this sports park facility is not managed properly. The theory used to answer the problem is (Haryadi & Setiawan, 2010) the core of the theory is that perception must be viewed contextually, must receive attention and have different individual experiences. The research method used is descriptive quantitative method, using the census method, and accidental sampling and cross tables, with the data collection technique: Questionnaire. The results of the discussion on the Perceptions of Sports and Recreation Park Visitors (TORR) stated that the complete and still functioning facilities were Basketball and Jogging, the rest were lacking or even incomplete and lacking or not functioning. Then it can be analyzed that the visitor's perception of the treatment is poor and not good, this is due to the non-existent budget factor. The Pekanbaru City Government should provide a routine budget for field maintenance operations and make policies on cleanliness and tidiness in the sports and recreation park (TORR) environment. The conclusion is that the visitor's perception of the sports park facilities is not good or even not good, because the budget factor is not there or not budgeted. Keywords: Perception, Facilities, Sports Park.